2006
DOI: 10.1183/09031936.06.00131505
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide reduces IL-18, IL-8 and TNF-α release from alveolar macrophages in interstitial lung disease

Abstract: Thalidomide exhibits diverse actions of anti-inflammation, immunomodulation and anti-angiogenesis. The efficacy of thalidomide treatment in sarcoidosis with lupus pernio is thought to be due to inhibition of tumour necrosis factor (TNF)-a. The mechanisms that underlie the properties of thalidomide are still unclear in interstitial lung disease.The current authors investigated the potential inhibitory effects of thalidomide at concentrations of 0.1, 0.01 and 0.001 mM on the production of transforming growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 36 publications
4
37
0
2
Order By: Relevance
“…Because TGF-␤ 1 does not stimulate the proliferation of ␣-SMA-positive myofibroblasts, we propose a dual inhibitory effect of Thal on IL-6-dependent proliferation and TGF-␤ 1 -dependent transdifferentiation of fibroblasts to myofibroblast, which may be the mechanism underlying the preventive and therapeutic effect of Thal on pulmonary fibrosis. Recently it has been reported that Thal reduced the production of TNF-␣, IL-8, and IL-18 from alveolar macrophages in pulmonary fibrosis (48). Especially as to TNF-␣, Thal has been reported to reduce its production in damaged lung (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Because TGF-␤ 1 does not stimulate the proliferation of ␣-SMA-positive myofibroblasts, we propose a dual inhibitory effect of Thal on IL-6-dependent proliferation and TGF-␤ 1 -dependent transdifferentiation of fibroblasts to myofibroblast, which may be the mechanism underlying the preventive and therapeutic effect of Thal on pulmonary fibrosis. Recently it has been reported that Thal reduced the production of TNF-␣, IL-8, and IL-18 from alveolar macrophages in pulmonary fibrosis (48). Especially as to TNF-␣, Thal has been reported to reduce its production in damaged lung (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…However, while one report has described that thalidomide inhibits IL-6, 12 another has described that thalidomide does not affect IL-6. 13 Since we did not measure IL-6 in this case, we were not able to draw any conclusions on this issue. Therefore, further analysis is required in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Macrophages are key inflammatory cells that have been documented to play a critical role in various airway disorders [13] . Upon stimulation with molecules such as LPS, these cells secrete an array of pro-inflammatory cytokines and oxidants, including TNF-α, IL-1β, and macrophage inflammatory protein-2 [14] . These proinflammatory cytokines genes are regulated by various transcription factors, including Egr-1 and NF-κB [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%